EFEKTIVITAS APLIKASI PUPUK KONVENSIONAL DAN “CONTROL RELEASE FERTILIZER” TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) - Mardiana Wahyuni; M. Fikih Nasution (Jurnal Agro Estate, 2018)
Oil palm nursery is a starting point in greatly determines for the success of planting in the field, while superior seeds are a large capital of the company to achieve high productivity and quality of palm oil. To get a really good, healthy, and uniform seed, strict sorting must be done. The study was conducted at the STIPAP Medan. The study period was 4 months, from April to August 2018. The study used Non Factorial Randomized Block Design (RBD) with 3 treatments and six replications, P1: Standard Fertilizer / Recommended PPKS, P2: Fertilizer Control Release Fertilizer (CRF) 1x application dose of 50 g / seed, P3: Fertilizer Control Release Fertilizer (CRF) 2x application, dose / application 50 g / seed. Parameter testing is compiled on the variance list with a level of 5% and 1% for the whole treatment. The best treatment found in P3 can increase plant height 59.29 cm (18%), stem circumference 15.88 cm (9%), leaf number 12.83 strands (7%), wet weight 188.56 gr (2%) and dry weight 52.45 gr (8%) were compared to the growth of IOPRI/PPKS Medan standard seedlings.